1994
DOI: 10.1073/pnas.91.18.8655
|View full text |Cite
|
Sign up to set email alerts
|

Cdk-interacting protein 1 directly binds with proliferating cell nuclear antigen and inhibits DNA replication catalyzed by the DNA polymerase delta holoenzyme.

Abstract: Cdk-interacting protein 1 (Cipl) is a p53-regulated 21-kDa protein that inhibits several members of the cyclin-dependent kinase (CDK) family. It was initlafly observed in complexes containing CDK4, cyclin D, and proliferating celi nuclear antigen (PCNA). PCNA, in conjunction with activator 1, acts as a processivity factor for eukaryotic DNA polymermse (po1) 8, and these three proteins constitute the p01 6 holoenzyme. Cipl is regulated by the tumor suppressor gene p53, a transcription factor that controls the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
278
2
2

Year Published

1997
1997
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(295 citation statements)
references
References 27 publications
13
278
2
2
Order By: Relevance
“…p21WAF1 directly interacts with PCNA and inhibits PCNA-dependent DNA replication (but not DNA repair) in in vitro systems (Flores-Rozas et al, 1994;Li et al, 1994;Waga et al, 1994). p53 protein has also been involved in directly inhibiting DNA replication through its association with the single-stranded DNA-binding protein complex RPA (Dutta et al, 1993) that is required for DNA unwinding during replication.…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…p21WAF1 directly interacts with PCNA and inhibits PCNA-dependent DNA replication (but not DNA repair) in in vitro systems (Flores-Rozas et al, 1994;Li et al, 1994;Waga et al, 1994). p53 protein has also been involved in directly inhibiting DNA replication through its association with the single-stranded DNA-binding protein complex RPA (Dutta et al, 1993) that is required for DNA unwinding during replication.…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…It was found that MyD118 and Gadd45 associate with PCNA Hall et al, 1995;Vairapandi et al, 1996), which plays a central role in DNA repair and DNA replication (Mossi and Hubscher 1998;Prosperi, 1997;Jonsson and Hubscher, 1997). MyD118 and Gadd45 were shown also to associate with the cyclin dependent kinase inhibitor p21 (Vairapandi et al, 1996), known to interact with PCNA and to inhibit DNA replication Li et al, 1994;Flores-Rozas et al, 1994). MyD118 and Gadd45 were also observed to enhance DNA excision repair activity in vitro Vairapandi et al, 1996).…”
Section: Myd116 ± Viral Homologs and A Protective Role In Apoptosismentioning
confidence: 99%
“…p21 has several cellular binding partners, including GADD45 damage response protein (Kearsey et al, 1995) and PCNA (Chen et al, 1995). The sequestration of PCNA by p21 from the replication machinery proteins inhibits DNA replication (Flores-Rozas et al, 1994) and interferes with the interaction of PCNA with DNA methyltransferases (Chuang et al, 1997). The loss of p21 leads to defective damage responses and loss of G 1 and mitotic checkpoint control (Brugarolas et al, 1995;Deng et al, 1995).…”
Section: Introductionmentioning
confidence: 99%